Topography of the insular cortex in heart rate control: high-precision mapping reveals critical role of the middle short gyrus - Tian, Xiaolin; Wang, Jing; Wang, Xiongfei; Yang, Xue; Li, Tianfu; Deng, Jiahui; Tang, Chongyang; Wang, Mengyang; Luan, Guoming (Frontiers in Neuroscience, 2025)
AimsAlthough accumulating evidence has demonstrated the involvement of the insular cortex in autonomic regulation, the precise functional topography of insular subdivisions mediating cardiovascular control remains controversial. This study aimed to investigate the role of the insula, with high anatomic precision, in regulating heart rate (HR).MethodsOverall, 487 electrical stimulations (E-stim) in patients with refractory epilepsy were used to investigate the incidence of evoked cardiac response after insula E-stim. Correlations between the parameters of E-stim, insula subdivision, and the HR shift profile were analyzed.ResultsBriefly, 40.8% of insula stimulations evoked a cardiac response. The left insula was more likely to induce cardiac responses. Compared to the electrode contacts in the declining HR group, those in the elevated HR group were predominantly distributed in the posterior insula. Notably, the middle short gyri can rapidly elicit a significant decrease in HR.ConclusionOur findings suggest that the middle short gyrus of the insula may serve as the primary cortical region mediating HR reduction. This provides new insights for the prevention and treatment of arrhythmias and sudden unexpected death in epilepsy (SUDEP).